Smoking, lower gastrointestinal endoscopy, and risk for colorectal cancer - Hoffmeister, Michael; Jansen, Lina; Stock, Christian; Chang-Claude, Jenny; Brenner, Hermann (Cancer epidemiology, biomarkers & prevention, 2014)
Background: Lower gastrointestinal endoscopy can decrease colorectal cancer risk strongly through detection and removal of adenomas. Thus, we aimed to investigate whether utilization of lower gastrointestinal endoscopy modifies the effect of lifetime smoking exposure on colorectal cancer risk in a population-based case-control study. - Methods: In this study from Southern Germany including 2,916 patients with colorectal cancer and 3,044 controls, information about lifetime smoking and other risk factors was obtained from standardized interviews. Self-reported endoscopies were validated by medical records. Multivariate logistic regression was performed to investigate associations of smoking with colorectal cancer risk after stratification by utilization of lower gastrointestinal endoscopy in the preceding 10 years. - Results: Median age of patients and controls was 69 and 70 years, respectively. Former regular smoking was associated with increased colorectal cancer risk in the group with no previous endoscopy [adjusted OR, 1.50; 95% confidence interval (CI), 1.28-1.75], whereas no association was found in the group with preceding endoscopy (OR, 1.05; CI, 0.83-1.33; P for interaction <0.01). Lower gastrointestinal endoscopy did not modify the association of smoking and colorectal cancer risk among current smokers and among the more recent quitters. - Conclusions: Our results suggest that the increased risk of colorectal cancer among former regular smokers is essentially overcome by detection and removal of adenomas at lower gastrointestinal endoscopy. However, risk of colorectal cancer was increased if smoking was continued into higher adult age. - Impact: The strong protective effect of lower gastrointestinal endoscopy may be compromised by continued smoking. Smoking cessation may increase the efficacy of lower gastrointestinal endoscopy. Cancer Epidemiol Biomarkers Prev; 23(3); 525-33. ©2014 AACR.